2019
DOI: 10.12659/msm.917970
|View full text |Cite
|
Sign up to set email alerts
|

Specific Biomarkers of Prostate Cancer-Associated Ischemic Stroke: A Case-Control Study

Abstract: Background Ischemic stroke in cancer patients is associated with poor prognosis. However, the specific biomarkers of cancer-associated ischemic stroke (CaIS) have not been well defined. Material/Methods A retrospective study was conducted on PCaIS patients. Clinical data and laboratory and imaging findings were collected. Multivariable logistic regression analysis was used to analyze the independent risk factors for PCaIS. A multiple model combining the independent risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…A few studies have reported associations between NLR and cancer-associated stroke incidence. Chen et al 22 reported that elevated D-dimer, total prostate-specific antigen and NLR were independent risk factors of ischaemic stroke among patients with prostate cancer, though this study did not adjust for cancer stage. In contrast, we used data on cancer stage, cancer site, and duration from diagnosis to ischaemic stroke, and applied survival tree analysis and multivariate Cox hazard regression models.…”
Section: Discussionmentioning
confidence: 84%
“…A few studies have reported associations between NLR and cancer-associated stroke incidence. Chen et al 22 reported that elevated D-dimer, total prostate-specific antigen and NLR were independent risk factors of ischaemic stroke among patients with prostate cancer, though this study did not adjust for cancer stage. In contrast, we used data on cancer stage, cancer site, and duration from diagnosis to ischaemic stroke, and applied survival tree analysis and multivariate Cox hazard regression models.…”
Section: Discussionmentioning
confidence: 84%
“…34 52 61 75 80 120 Chen et al studied mean platelet count as a predictor for ischemic stroke in a group of prostate cancer patients without traditional risk factors for stroke. 34 Li et al and Shi et al investigated postoperative VTE in cervical cancer and glioma patients, 52 75 respectively, while Sutandyo et al investigated chemotherapy-related VTE 120 and von Tempelhoff et al investigated patients undergoing both surgery and chemotherapy. 80 Monreal et al studied catheter-related deep venous thrombosis (DVT).…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified 26 studies on mean and median platelet count and association with thrombosis, mean platelet count and standard deviation could be retrieved for meta-analysis in 14 studies. 27 29 34 36 52 61 69 75 80 82 85 108 112 120 Thirteen of these studies rated good or fair, 29 34 36 52 61 69 75 80 82 85 108 112 120 while one study rated poor. 27 A substantial between-study heterogeneity was observed in 14 studies (Q = 166.32 on 13 df; p = 0.00; I 2 = 93.44%, p = 0.00), explaining why a pooled SMD was estimated using a random-effects model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations